Isothermal and non-isothermal crystallization kinetics of PLA/PBS blends with talc as nucleating agent - Runglawan Somsunan (2019)
© 2019, Akadémiai Kiadó, Budapest, Hungary. The isothermal and non-isothermal crystallization kinetics of PLA/PBS at the blend ratio of 90/10 by mass containing 0.1% of talc was studied by differential scanning calorimetry. In this study, Avrami and Tobin equations were used to explain isothermal crystallization kinetics. The results of both theoretical models offered the same trend results which were the different crystallization temperatures influenced crystallization rate and the amount of crystallinity. It was found that at 100 °C is the temperature for the fastest of the completion of the crystallization blending process. Both models were also used to calculate the overall kinetic rate constant, n value, half-time of crystallization and growth rate. They indicated that growth dimension was three-dimensional which is the spherulitic growth from instantaneous nuclei of heterogeneous nucleation and occurred from talc. For non-isothermal crystallization kinetics, Jeziorny and Ozawa equations were used to explain. The results from Jeziorny equation show that there are two stages of crystallization at high cooling rate, the straight line in the primary stage followed by the nonlinear line in the secondary stage. It was also found that Jeziorny crystallization rate increased when the cooling rate increased. However, the Ozawa model was inappropriate for describing the non-isothermal crystallization for these blends.